Phase and structure engineering of copper tin heterostructures for efficient electrochemical carbon dioxide reduction - Pengtang Wang (Nature Portfolio, 2018)
While CO2 removal will play a crucial role in limiting climate change, it is challenging to understand the factors that control materials’ selectivity to convert CO2 to valuable products. Here, authors show copper and tin oxide interfaces to impact activities for CO2 reduction products.